Pengembangan Sistem Informasi Manajemen Kearsipan Surat Menyurat Berbasis Framework Codeigniter untuk KPH-KTT - Arif Fadllullah; Mulyadi Mulyadi; Rochaniati Rochaniati; Farhan Muhammad Nabil (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
In carrying out their functions as forest managers and supervisors, UPT KPH KTT employees are required to always be active and have high mobility. However, this mobility will be disrupted when the management of employees and archives at UPT KPH KTT is still not running optimally. In addition, a manually recapitulated letter will make it difficult for the mail administration to search for the required letter archive. Based on these problems, this research proposes to develop SIM-KSM based on the MVC (model-view-controller) CodeIgniter framework for UPT KPH KTT. The design in making this application uses the SDLC (Software Development Life Cycle) method and is tested by compatibility, black-box, and usability testing for several sample of respondents. The results of the compatibility test show that this application can be accessed on various types of web browsers on PC/Laptop/smartphone. The black-box test results show that the application workflow is valid for all designed business processes. The results of the usability test show that this application is in the range of grade B with a value of 81.2. These results indicate that the interface and business processes in this application can work well and can be used by users easily.